Retail central bank digital currency: Has its time come? - Pierre L. Siklos (Centre for International Governance Innovation (CIGI), 2022)
As central banks around the world prepare to launch central bank digital currencies (CBDCs), this paper looks at issues surrounding a retail version of CBDCs that would complement notes and coins for consumers. To build the public's trust in this type of digital currency, concerns such as loss of privacy and security of financial transactions must first be addressed. In addition to these concerns, CBDCs carry the potential risks of overburdening central banks and disrupting cross-border transactions. These and other challenges can be overcome by ensuring the right regulatory and supervisory measures are in place before CBDCs take hold.
Keywords: 330